VD_FINDINFO Jug / 2023 / 401 vom 20. Mai 2021 - VD Tribunal cantonal (2021)
REJET DE LA DEMANDE, LIBÉRATION CONDITIONNELLE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 221 al. 1 let. c CPP (CH)